Composition and Characteristics of Some Seed Oils - Sami Erol, Ahmet; Musa Ozcan, Mehmet; Er, Fatih (Asian Journal of Chemistry, 2010)
Physico-chemical characteristics and fatty acid composition of some seed oils (corn, cotton, olive, poppy, pumpkin, rape, safflower, sunflower, tea seed, walnut and wheatgerm) were determined. The oil content of samples ranged from 10.73 % (wheatgerm) to 61.3 % (walnut). Refractive index, relative density, saponification and iodine values were determined in the seed oils. The main fatty acids identified by gas chromatography were palmitic acid, oleic acid and linoleic acid. The linoleic acid content of oils were found high compared with other acids.